Contemporary Global Ummatic Challenges and Future Vision: Human (Under-) Development and Clash of Civilisation - Muhammad Ahsan (Journal of Political Studies, 2010)
The underdeveloped, internally weak, frustrated and conflict-ridden contemporary Muslim World is in a state of crisis. The Muslim World, which has suffered at the hands of the West in the past and remains, even today, weak materially, economically, technologically and militarily, is now being projected as a threat to the West. The Ummatic efforts to rediscover its identity and set its own house in order are looked upon as a challenge to the West. For Muslims, it is habitual to accuse major global powers for all their ills. Possibly, this excuse may give them some relief; it does not provide the solution to their deep rooted internal problems. These internal ills not only cause corrosion to the Ummah but also open the doors for external powers to meddle in their internal affairs. How did the Muslim World get into this situation and what are the possible solutions to come out of these crises? And also, how can the Muslim World regain the dignity of its glorious past to lead in global affairs. Therefore, in the light of these questions, the proposed paper will focus on: i) the analysis of the challenges faced by the Muslim Ummah, ii) possible solutions for these challenges, and, iii) the presentation of a three phased plan stretching over the next 50 years. In the light of the analysis, the plan will present major steps to be taken during respective phases as well as the ways and means to finance various proposed programme.